Optimization of Reading Comprehension in Primary Education through the Speed Reading Method (Jurnal Ilmiah Sekolah Dasar, 2025)
Many students are only able to read mechanically without being able to interpret or conclude the contents of the text well, which has an impact on their low critical and analytical thinking skills. In addition, the low interest in reading among students further worsens this situation, considering that reading habits are one of the main determinants in the development of literacy skills. This study aims to analyze the effect of implementing the speed reading method on students' abilities in interpreting, summarizing, comparing, and concluding the contents of reading texts at a higher cognitive level in Elementary Schools. Using the quasi-experimental method of the pretest-posttest control group model, this study compares the experimental class that applies the speed reading method with the control class that uses the conventional method. The sample consisted of 57 students in grade, namely the VA class as an experimental class consisting of 28 students and VB as a control class consisting of 29 students. Data is collected through testing and documentation. The results showed a significant difference between the average posttest score of the experimental class (78.57) and the control class (67.59), with tcount (3.643) > ttable (2.004) at a significance of 0.001 < 0.05. The speed reading method has been proven to improve students' ability to interpret, summarize, compare, and summarize the content of the text. In addition, this method also increases students' enthusiasm, motivation, and interest in reading. Despite the challenges in its implementation, the results of the study show that the speed reading method is effective in improving the ability to understand the content of reading texts in grade V elementary school students.